Strengthening Students’ Spatial Awareness through Eco-Pedagogical Activities: A Case Study at the Kuala Langat Learning Centre, Malaysia (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Spatial awareness is essential for developing students’ understanding of their environment and strengthening their national identity. This study aimed to enhance spatial awareness among Indonesian migrant students at the Kuala Langat Learning Centre, Malaysia, through an eco-pedagogical approach as a means of fostering love for the homeland. The program involved 23 primary school students and employed several methods: information sessions, question-and-answer discussions, learning assistance, and evaluation. The evaluation results indicated that 78% of students demonstrated improved ability in recognising Indonesian geographical regions, and the average post-activity assessment score increased by 22% compared to the initial test. Furthermore, students’ reflective discussions and creative projects (maps and posters) showed stronger ecological awareness and appreciation of Indonesia’s cultural and environmental diversity. The eco-pedagogical approach thus proved effective in improving spatial understanding and instilling national values. These findings highlight the potential of experience-based learning to support migrant students in strengthening their sense of identity and patriotism.